The gendered society - Kimmel, Michael S. (Oxford University Press, 2004)
Thoroughly updated and revised, the second edition of "The Gendered Society" explores current thinking about gender, both inside academia and in our everyday lives. Part I examines the latest work in biology, anthropology, psychology, and sociology; Part II provides an original analysis of the gendered worlds of family, education, and work; and Part III focuses on the gendered interactions of friendship and love, sexuality, and violence. As a result of his research, author Michael S. Kimmel makes three claims about gender. First, he argues that the differences between men and women are not as great as we often imagine, and that in fact women and men have far more in common with one another than we think they do. Second, he challenges the notions of the many pop psychologists who suggest that gender difference is the cause of the dramatic observable inequality between the sexes. Instead, Kimmel reveals that the reverse is true: gender inequality is the cause of the differences between women and men. Third, he argues that gender is not simply an aspect of individual identity but is also an institutional phenomenon, embedded in the organizations and institutions in which we interact daily. Kimmel concludes with a brief epilogue looking ahead to gender relations in the new century. The second edition includes a new chapter, The Gendered Body, and a sharper critique of biological differences. "The Gendered Society, 2/e", is a well-reasoned, authoritative, and keenly animated statement about contemporary gender relations, written by one of the country's foremost thinkers on the subject. It is an essential text for both scholars and students alike. Kimmel's companion book, "The Gendered Society Reader, 2/e, (OUP, 2003)", provides a perfect complement for classroom use.